2018
DOI: 10.3389/fmicb.2018.01920
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Diversity in Chinese Rushan Cheese From Different Geographical Origins

Abstract: Rushan cheese, an essential part of the Bai culture, has been produced and consumed for centuries by the Bai people living mostly in Yunnan province of China, however, studies on the naturally occurring microbial communities of Rushan cheese are lacking. In this study, we applied high throughput sequencing technique to analyze the microbial compositions of Rushan cheese samples from three different geographical origins (i.e., Weishan, Eryuan, and Jianchuan). The microbiota in Weishan, Eryuan and Jianchuan Rush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
(30 reference statements)
2
11
1
Order By: Relevance
“…Unlike rennet‐curd or long‐ripe goat cheese, milk cake is a fresh, traditional acid‐curd goat cheese prepared by the addition of a fermented acid solution (Xue, Yang, Wang, Guo, & Shao, 2018). This preparation may be an important reason for its moderate and mild flavor.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike rennet‐curd or long‐ripe goat cheese, milk cake is a fresh, traditional acid‐curd goat cheese prepared by the addition of a fermented acid solution (Xue, Yang, Wang, Guo, & Shao, 2018). This preparation may be an important reason for its moderate and mild flavor.…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported that Acinetobacter isolates from mozzarella cheese were proteolytic [63]. Acinetobacter has been detected by high-throughput sequencing in several studies, including raw bovine milk from tanker trucks and silos [6], vats and other environmental samples [7], milk, curd and Pico cheese (an artisanal cheese manufactured from raw cow's milk in small dairy units in Portugal) [11,14] and in Chinese Rushan cheese [18]. The presence of Acinetobacter in Paipa cheese could be important not only as an indication of poor hygiene and environmental contamination, but also because members of this group may also carry antibiotic resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput sequencing (HTS) has become a powerful culture-independent approach that can be used to obtain snapshots of microbial communities from food systems. In the milk and dairy industry, numerous studies based on HTS technologies have been carried out [3] with different purposes, e.g., to decipher the microbiota from farm environments and animals [4], raw and pasteurized milk [5], transportation tanks, vats, utensils and cheese production facilities [6][7][8] and the variations associated with season [6] or animal feeding [9], to establish relationships between microbial communities in the raw materials, the environment and the finished product [8][9][10], to study the changes in the bacterial communities associated with cheese-making [9,11] and cheese ripening processes [9,[12][13][14][15], or to determine the microbial composition of cheeses and cheese varieties [16][17][18][19]. Furthermore, HTS studies can also provide information on adventitious or previously overlooked microbiota or the presence of pathogenic or spoilage bacteria in the cheese and dairy environment [2,3,11,14,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, L. kefiranofaciens was barely present in 17 tarag samples collected from various regions of Mongolia and China and analyzed with pyrosequencing, leading to the conclusion that geographical origin may influence the microbial biodiversity [78]. Additionally, L. kefiranofaciens was detected in Rushan cheese samples produced in Yunnan province in China using 16S rRNA gene sequencing [79] and in a Camembert-type cheese made in Shanghai, China, by PCR-DGGE, and strains were isolated using acidified MRS containing 0.4 mg/mL nystatin after growth at 37 • C for 48 h anaerobically [80].…”
Section: Origin Detection Number Of Isolates Referencementioning
confidence: 99%